Impact of an interprofessional shared decision-making and goal-setting decision aid for patients with diabetes on decisional conflict – study protocol for a randomized controlled trial - Yu, Catherine H; Ivers, Noah M; Stacey, Dawn; Rezmovitz, Jeremy; Telner, Deanna; Thorpe, Kevin; Hall, Susan; Settino, Marc; Kaplan, David M; Coons, Michael; Sodhi, Sumeet; Sale, Joanna; et al. (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Competing health concerns present real obstacles to people living with diabetes and other chronic diseases as well as to their primary care providers. Guideline implementation interventions rarely acknowledge this, leaving both patients and providers feeling overwhelmed by the volume of recommended actions. Interprofessional (IP) shared decision-making (SDM) with the use of decision aids may help to set treatment priorities. We developed an evidence-based SDM intervention for patients with diabetes and other conditions that was framed by the IP-SDM model and followed a user-centered approach. Our objective in the present study is to pilot an IP-SDM and goal-setting toolkit following the Knowledge-to-Action Framework to assess (1) intervention fidelity and the feasibility of conducting a larger trial and (2) impact on decisional conflict, diabetes distress, health-related quality of life and patient assessment of chronic illness care. Methods/Design A two-step, parallel-group, clustered randomized controlled trial (RCT) will be conducted, with the primary goal being to assess intervention fidelity and the feasibility of conducting a larger RCT. The first step is a provider-directed implementation only; the second (after a 6-month delay) involves both provider- and patient-directed implementation. Half of the clusters will be assigned to receive the IP-SDM toolkit, and the other will be assigned to be mailed a diabetes guidelines summary. Individual interviews with patients, their family members and health care providers will be conducted upon trial completion to explore toolkit use. A secondary purpose of this trial is to gather estimates of the toolkit’s impact on decisional conflict. Secondary outcomes include diabetes distress, quality of life and chronic illness care, which will be assessed on the basis of patient-completed questionnaires of validated scales at baseline and at 6 and 12 months. Multilevel hierarchical regression models will be used to account for the clustered nature of the data. Discussion An individualized approach to patients with multiple chronic conditions using SDM and goal setting is a desirable strategy for achieving guideline-concordant treatment in a patient-centered fashion. Our pilot trial will provide insights regarding strategies for the routine implementation of such interventions in clinical practice, and it will offer an assessment of the impact of this approach. Trial registration Clinicaltrials.gov Identifier: NCT02379078 . Date of Registration: 11 February 2015.